The Failure of Male Domination in Brave (2012) Movie - Marta, Silvia (Faculty of Arts and Education, 2023)
Many characters in literature often represent dominating characters, have strong capacity, and always use violence to solve problems. Brave movie is a story of a woman who wants to break free from the normal norms. This research was intended to see the failure of many characters in showing domination. Using descriptive qualitative as the research method, this study was aimed to decode the man's failure in dominating in Brave movies. With the help of Hall’s representation theories and Collin’s masculinity theory, this research will surely show the characteristics of the topics. This research showed that the main characters showed failures in giving domination to the main characters. Through three characteristics which are care responsibility, violence as manly, and danger as exciting, this research fulfills the representation of man's failure in domination. Keywords: characteristic, empowerment, feminism, gender, movie